Public Relation Management in Developing Organizational Behavior - Mukhtar Mukhtar; Risnita Risnita; Cittra Juniarni (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
This research described basically and found out concept of public relation management in order to determine how the public relation management in developing organizational behavior. This research was located in State Islamic Senior High Schools in Jambi Province consisting of MAN 1 Jambi, MAN 1 Batanghari, and MAN 1 Tebo. This research is qualitative descriptive research. Data collection techniques were using observation, interview and documentation. Data analysis used combined Miles Huberman and John Creswell model. Data validity technique used data triangulation. Results of the research show that public relation management can be seen from implementation of small group communication planning, execution of special events of public relations, media use, and evaluation on Islamic school program. Organizational behavior can be seen from mutual communication with the society, adjustment on public needs, support by the society and clear targets. Conclusion of this research shows that the public relation management can develop organizational behavior in State Islamic Senior High Schools in Jambi Province. Implication of this research shows that the public relation management can develop the organizational behavior.